Examining the Relationship Between Urban Park Quality and Residents’ Health in South Korean Cities Using Public Data - Yoonku Kwon; Kyeongjun Park; Ingu Kang; Changyeong Shin; Giyeol Lee; Sanghoon Lee (Land)
Urban parks are critical components of green infrastructure, supporting recreation and public health. This study investigates the association between urban park quality and health outcomes in 85 South Korean cities, utilizing a localized version of the ParkScore Index. The Korean ParkScore evaluates five dimensions: acreage, amenities, investment, accessibility, and equity. The health indicators include municipal-level rates of mental health disorders (anxiety, depression, insomnia, ADHD, and schizophrenia) and obesity. Pearson’s correlation analysis revealed significant negative associations between ParkScore rankings and mental health indicators, particularly depression and anxiety. Higher-quality, more accessible parks correlated with lower levels of psychological distress, emphasizing the public health benefits of urban green spaces. While the cross-sectional design limits causal inference, the results support the role of urban parks as essential infrastructure for mental well-being. The findings underscore the need for equitable and data-driven urban park policies in fostering health-supportive urban environments and highlight the importance of considering specific ParkScore dimensions in urban planning.